Development of an instrument measuring Navigation Health Literacy in the Health Literacy Survey 2019. (30th September 2020) - Griese, L; Schaeffer, D; Berens, E; Nowak, P; Pelikan, J
Abstract: Background: Complex and intransparent structures are the main reasons why it is difficult for patients to navigate the healthcare system. Thus, patients need specific competencies to deal with health information related to orientation and finding the right pathways through the healthcare system. The aim was therefore to develop an internationally applicable instrument for measuring Navigation Health Literacy (N-HL) within the European Health Literacy Survey 2019 (HLS19). Methods: Item development was conducted by a working group within the HLS19 consortium. It consisted of a scoping review on definitions, concepts and instruments, development of a definition of N-HL, a concept mapping and first item formation. The items were further developed by an evaluation by 6 experts, 4 focus group discussions, and feedback from members of the HLS19 Consortium. Finally, the feedback was integrated into the instrument and pretested in 33 interviews. Results: 10 publications providing concepts and instruments assessing navigational aspects were identified, but the process of dealing with information was scarcely considered. Therefore, based on the HL definition by Sørensen et al. (2012) N-HL was defined as difficulties in finding, understanding, appraising and applying health information for navigating the healthcare system. In total, 10 tasks at system, organization and interaction level emerged within this definition, on which the final instrument is based. Of 15 initial items, 3 items were assessed as not relevant by experts. The feedback from focus group and HLS19 discussions lead to further revision and addition of items. The final instrument consists of 12 items which proved to be applicable in the pretest. Conclusions: The instrument can be used to assess N-HL in international population studies and has been used within the HLS19 study to generate internationally comparable data on N-HL for the first time. By that it can form a basis for intervention development and monitoring. Key messages: An instrument for measuring navigation health literacy (N-HL) is important to assess and monitor difficulties of patients to navigate the healthcare system and to underpin intervention development. The N-HL instrument of HLS19 can be used to assess N-HL in international population studies and provides internationally comparable data.